First record of the big-scale sand smelt (Atherina boyeri Risso, 1810, Pisces: Atherinidae) from Porsuk Dam Lake, Türkiye - Benzer Semra (Oceanological and Hydrobiological Studies)
This study represents a preliminary report on the occurrence of Atherina boyeri in the Porsuk Dam Lake, with a total of 420 individuals obtained from local fishermen between May and July 2023. Of these specimens, 34.76% (146 individuals) were males and 65.24% (274 individuals) were females, resulting in a calculated sex ratio (females:males) of 1:0.53. The total length of the sampled fish ranged from 6.06 to 10.84 cm and their weight ranged from 1.34 to 8.60 g. The length–weight relationship (LWR) based on total length was calculated as W = 0.00001003 L2.9359 for the female population, W = 0.00000525 L3.0665 for the male population, and W = 0.00000474 L3.0975 for the entire population. The exponential value of the total length to weight ratio, denoted as ‘b’, was determined as 3.0975, indicating isometric growth for the species. The mean value of the condition factor for females, males, and all individuals of A. boyeri was determined as 0.755 ± 0.085, 0.710 ± 0.076, and 0.740 ± 0.084, respectively. This study not only provides preliminary and valuable data on the presence of A. boyeri in the Porsuk Dam Lake, but also offers a significant perspective on the biodiversity of the new habitat. The findings of the study are considered to be applicable to local fisheries management authorities and decision-makers to ensure the sustainability of fishery resources and the implementation of appropriate fisheries management strategies.